20-4(w+1)=9w-4(9+w)

Simple and best practice solution for 20-4(w+1)=9w-4(9+w) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20-4(w+1)=9w-4(9+w) equation:


Simplifying
20 + -4(w + 1) = 9w + -4(9 + w)

Reorder the terms:
20 + -4(1 + w) = 9w + -4(9 + w)
20 + (1 * -4 + w * -4) = 9w + -4(9 + w)
20 + (-4 + -4w) = 9w + -4(9 + w)

Combine like terms: 20 + -4 = 16
16 + -4w = 9w + -4(9 + w)
16 + -4w = 9w + (9 * -4 + w * -4)
16 + -4w = 9w + (-36 + -4w)

Reorder the terms:
16 + -4w = -36 + 9w + -4w

Combine like terms: 9w + -4w = 5w
16 + -4w = -36 + 5w

Solving
16 + -4w = -36 + 5w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-5w' to each side of the equation.
16 + -4w + -5w = -36 + 5w + -5w

Combine like terms: -4w + -5w = -9w
16 + -9w = -36 + 5w + -5w

Combine like terms: 5w + -5w = 0
16 + -9w = -36 + 0
16 + -9w = -36

Add '-16' to each side of the equation.
16 + -16 + -9w = -36 + -16

Combine like terms: 16 + -16 = 0
0 + -9w = -36 + -16
-9w = -36 + -16

Combine like terms: -36 + -16 = -52
-9w = -52

Divide each side by '-9'.
w = 5.777777778

Simplifying
w = 5.777777778

See similar equations:

| 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 |

Equations solver categories